Jurnal Ujian - novinda amry (ITCOMS, 2011)
Dr. Tanya Jakimow (Unversity of New South Wales, Australia)/ ConfirmedProf.Dr. Eko Prasojo (Chairperson of Indonesian Association of Public Administration/ IAPA, Indonesia; Dean of FISIP UI)/ ConfirmedProf. Dr. Bambang Sumintono (University Malaya, Malaysia)/ ConfirmedDr. Riant Nugroho (Policy Analyst)/ Confirmed.